1996
DOI: 10.1253/jcj.60.841
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Head-up Tilt Testing in Patients With Syncope of Undetermined Etiology

Abstract: Indices of heart rate variability are non-invasive indicators of neural control of the heart. To investigate the significance of changes in heart rate variability in neurally mediated syncope, we performed head-up tilt testing in 45 patients with syncope of undetermined etiology. Seventeen patients showed a negative response and 28 showed a positive response; 18 had a vasodepressor response (systolic blood pressure dropped > or = 50% without a decrease in heart rate) and 10 had a vasovagal response (systolic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Grubb et al [9] and Takase et al [21] showed that the pulsatility index in the middle cerebral artery increased during HUT or standing and noted an increase in cerebral vascular resistance in patients with syncope. On the other hand, Levine et al [15] argued that increased cerebral vasoconstriction during orthostatic stress is not by itself sufficient to cause syncope.…”
Section: Discussionmentioning
confidence: 99%
“…Grubb et al [9] and Takase et al [21] showed that the pulsatility index in the middle cerebral artery increased during HUT or standing and noted an increase in cerebral vascular resistance in patients with syncope. On the other hand, Levine et al [15] argued that increased cerebral vasoconstriction during orthostatic stress is not by itself sufficient to cause syncope.…”
Section: Discussionmentioning
confidence: 99%
“…We used a passive head-up tilt test to stimulate adaptation reactions in cardiovascular autonomic control and evaluate it (Montano et al 1994, Takase et al 1996, Suzuki et al 2006. The electrocardiogram (ECG), PPGs from the middle finger of the right and left hand (denoted below as PPG(R) and PPG(L), respectively), PPG from the earlobe (denoted below as PPG(ear)), and respiration were simultaneously recorded during 10 min in healthy subjects at each stage of the head-up tilt test.…”
Section: Signal Recordingmentioning
confidence: 99%
“…Even if the model is limited to autonomic control of circulation, the simplification is necessary, which leads to a limited description of a specific pathology or effect. For example, a passive head-up tilt test [22][23][24][25] is one of the most common tests to investigate autonomic control adaptation both in medical practice and fundamental studies. There are a number of cardiovascular models [26][27][28][29] capable of precise simulation of arterial pressure (AP) and heart rate dynamics during a passive tilt test.…”
mentioning
confidence: 99%